The Impact of Internal Control and Individual Morals on Fraud: An Experimental Study - Efrizon, Efrizon; Febrianto, Rahmat; Kartika, Rayna (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This study aims to obtain evidence to determine whether there are differences in the likelihood to commit fraud between individuals under the conditions of present and absent internal control and between individuals with high and low levels of individual morality. The study also aims to determine whether the interaction between individual morality and internal controls lead to fraud. Results show differences among individuals under the conditions of present or absent internal control to commit fraud. Moreover, there are differences among individuals who have high and low levels of individual morality to commit fraud. Finally, results reveal that the interaction between individual morality and internal controls lead to fraud.   Keywords : Fraud; internal control; individuals moral